Human molecular genetics 3 - Strachan, T. (Garland Press, 2004)
There are new chapters on cells and development and on functional genomics. The sections on complex diseases have been completely rewritten and reorganized, as has the chapter on Genome Projects. Other changes include a new section on molecular phylogenetics (Chapter 12) and the introduction of 'Ethics Boxes' to discuss some of the implications of the new knowledge. Virtually every page has been revised and updated to take account of the stunning developments of the past four years since the publication of the last edition of Human Molecular Genetics.